Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12883-022-02671-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peer education based on Pender’s health promotion model on quality of life, stress management and self-efficacy of patients with multiple sclerosis: a randomized controlled clinical trial

Abstract: Background As a chronic, disabling disease, multiple sclerosis (MS) has challenged healthcare systems in many ways. MS adversely affects patients’ quality of life and self-efficacy and results in psychological stress. The present study was conducted to investigate the effect of peer education based on Pender’s health promotion model on the quality of life, stress management, and self-efficacy of patients with MS in the south of Iran. Methods The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…As regards to types of MS, the finding of present study revealed that about two thirds of the studied adolescents had relapsing remitting MS, this result was in agreement with study by Bijani et al, (2022) who conducted study about " The effect of peer education based on Pender's health promotion model on quality of life, stress management and self-efficacy of patients with multiple sclerosis" and reported that two thirds of the studied adolescents had relapsing remitting MS.…”
Section: Onsupporting
confidence: 91%
See 1 more Smart Citation
“…As regards to types of MS, the finding of present study revealed that about two thirds of the studied adolescents had relapsing remitting MS, this result was in agreement with study by Bijani et al, (2022) who conducted study about " The effect of peer education based on Pender's health promotion model on quality of life, stress management and self-efficacy of patients with multiple sclerosis" and reported that two thirds of the studied adolescents had relapsing remitting MS.…”
Section: Onsupporting
confidence: 91%
“…Less than 1% of all pediatric MS patients have an onset before the age of 10 years. Gender ratio varies with age at onset (Bijani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pertaining to studied adolescents QOL regarding their emotional well -being, the current study demonstrated that few of the studied adolescents total score of QOL was best and less than one fifth of them their QOL total was worse regarding their emotional well-being in pre nursing intervention, while less than two thirds of them their quality of life total score was best and none of them was worse in post nursing intervention. This finding was consistent with study by Bijani et al, (2022) who conducted study about " The effect of peer education based on Pender's health promotion model on quality of life, stress management and self-efficacy of patients with multiple sclerosis" and illustrated that more than two thirds of the studied patients had poor quality of life pre program, while post program more than half of them had good quality of emotional well -being. Moreover, there was high statistical significant difference (p<0.001) between pre and post intervention regarding their emotional well -being.…”
Section: Table (3): Tablesupporting
confidence: 90%
“…Less than 1% of all children with MS experience symptoms before the age of 10. The age of onset affects the gender ratio (Bijani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The present study explored the effectiveness of multimediabased peer education on anxiety in Covid-19 patients along with the usefulness of this peer support as a form of mental health support for these patients. Studies have shown that use of the experiences of peer groups, adequate education and information related to the disease, control and follow-up care through people who have practical knowledge of the disease and are affected by it would improve the health status of patients (25).…”
Section: Discussionmentioning
confidence: 99%